Perbedaan Hasil Belajar IPA dilihat dari Penggunaan Media Konkret dengan Media Audio-Visual pada Peserta Didik Kelas IV SDN-1 Panarung Palangkaraya - Desy Desy; Diplan Diplan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine whether or not there are differences in learning outcomes of science seen from the use of concrete media with audio-visual media in fourth-grade students of SDN 1 Panarung 2015/2016 Academic Year. The research method in this study is a quantitative correlation. The results of the study show that there are differences in learning outcomes of science seen from the use of concrete media with audio-visual media in fourth-grade students of SDN 1 Panarung 2015/2016 Academic Year. with a count of t count of 6.012 and t table of 2,000 at N = 59 with a significant level of 5% for 2 tails which means tcount> t table or 6.012> 2,000.